Retrospective study of cisplatin plus radiotherapy toxicities in locally advanced squamous cell carcinoma of the head and neck – ReCisTT study - Varges Gomes, Ana; Castro, Gilberto; de Oliveira, Thiago Bueno; Colmenero, Ana Medina; Ribeiro, Leonor; Psyrri, Amanda; Magné, Nicolas; Plana Serrahima, Maria; Marinho, Joana; Giglio, Raul; Iglesias Rey, Leticia; Angel, Martín; et al. (Frontiers in Oncology, 2024)
IntroductionSquamous cell carcinoma of the head and neck (SCCHN) is a multifactorial disease involving genetic and environmental factors representing one of the most frequent cancer-related deaths worldwide. Tobacco and alcohol use account for most SCCHN, while a growing subset of oropharyngeal cancers is causally associated with human papillomavirus (HPV) infection. Despite improvements in overall survival, patients with HPV-negative locally advanced (LA) SCCHN continue to have a poor prognosis. For these patients, the standard of care is radiotherapy with concurrent chemotherapy (RCT).MethodsThis retrospective, multicenter, and observational study analyzed the treatment compliance of 326 patients with LA-SCCHN who underwent RCT between January 1st, 2014, and June 30th, 2017. This study also evaluated the potential factors associated with treatment compliance, the compliance impact on clinical response, and the main toxicities experienced by patients.ResultsA total of 274 (84%) patients were compliant and received the planned dose of cisplatin. Overall, 957 adverse events were reported in 98.2% of patients during the study. The overall response rate was 80.2%, with 60.4% of patients achieving a complete response.DiscussionDespite the high treatment compliance, 62.6% of adverse events reported were related to cisplatin. Identifying risk factors associated with non-compliance could enable physicians to identify ineligible patients for cisplatin-based RCT and prevent patients from receiving inadequate treatment leading to severe adverse events..